Analyzing vocational education and training systems through the lens of political science - Graf, Lukas [Verfasser]; Lohse, Anna Prisca [Verfasser] (My University, 2022)
„The discipline of political science has a long-standing interest in the comparative study of governance structures and policy reforms in vocational education and training (VET). In analyses of VET systems, political science scholars often rely on historical institutionalism. Historical institutionalism is a theoretical framework that seeks to understand institutional stability and change in light of political coalitions, temporal processes, path dependencies, and critical junctures. This chapter introduces historical institutionalism as an important political science perspective frequently used to analyze skill formation policies. We first provide a theoretical introduction to historical institutionalism. This is followed by a review of its applications in education research. Finally, we conduct an illustrative case study, which exhibits this perspective’s analytical capacities in the comparison of national VET policies. Focusing on the cases of Germany and Switzerland, our empirical analysis explores how both countries’ VET systems have responded to academization pressures brought about by the rise of the knowledge economy. Drawing on key concepts of historical institutionalism, we find that different modes of gradual institutional change are at play in the two countries. While Germany has carried out reforms in the form of policy layering, the dominant trajectory of change in the case of Switzerland is policy conversion. The respective modes of change derive from historically transmitted actor constellations and institutional configurations. The chapter concludes with reflections on the use of historical institutionalism in the realm of skill formation policies more generally.“ (authors’ abstract; BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; S System beruflicher Bildung; 370; Berufsbildungsforschung; Berufsbildungssystem; Vergleichende Berufsbildungsforschung; Politikwissenschaft; Institutionalismus; Akademisierung; Bundesrepublik Deutschland; Schweiz